Product review: avelumab, an anti-PD-L1 antibody - Julie M. Collins; James L. Gulley (Taylor & Francis Group, 2019)
Although immunotherapies have been employed for many decades, immune checkpoint inhibitors have only recently entered the oncologic landscape. Avelumab is a fully human monoclonal antibody that blocks the interaction between PD-L1 on tumor cells and PD-1 on T cells, thereby inhibiting immunosuppression in the tumor microenvironment and reducing tumor growth. Most early clinical trials of avelumab as monotherapy and in combination regimens were part of the international JAVELIN clinical trial program, which included more than 7000 patients in more than 30 trials with at least 15 tumor types. Avelumab has been approved by the U.S. FDA for the treatment of metastatic Merkel cell carcinoma and metastatic urothelial carcinoma that has progressed during or following treatment with a platinum-based regimen. Its acceptable safety profile and ability to induce durable responses in otherwise deadly tumors provide the rationale for its use in other tumor types and in combination with other therapies.